The Relationship between Problem-Solving Ability and Students' Characters Based on Islamic Perspectives - Huda, Syamsul; Syahrul, Muhammad; Firmansyah, Mu'min; Ramadhani, Rahmi; Prasetiyo, Andika Eko (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2019)
The purpose of this study was to analyze the mathematical problem-solving ability and characters of students who were taught using problem-based learning and ordinary learning based on Islamic perspectives. The instrument used in this study was a test of problem-solving ability and a students’ character questionnaire. This research was a quasi-experimental research with pre-test and post-test control group design. The sample of this research was 84 students from Private Islamic School in Medan, North Sumatera, by using a purposive sampling technique. The data in this research was declared homogenous and normal after being tested using the Levene’s Test and Kolmogorov-Smirnov Test. The hypothesis analyzes used was the Two Way-ANOVA test assisted by SPSS 25. The result showed that there was an improvement in mathematical problem-solving ability and students' characters through problem-based learning based on Islamic perspectives. However, there was no interaction between students' gender and problem-solving ability and character improvement based on Islamic perspectives. The gender factor in problem-based learning was not related to students’ cognitive and affective aspects. Each student with any gender had difference characters, especially related to Islamic perspectives. This research-proven that problem-based learning model had an important role in teaching and learning, and it can be used to improve students' mathematical and character problem-solving ability.